2021
DOI: 10.3390/f12030349
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Dynamics of Above-Ground Litter Production and Decomposition from Eucalyptus grandis Hill ex Maiden and Pinus taeda L., and Their Contribution to Soil Organic Carbon

Abstract: The replacement of native pasture by exotic commercial forest species is an infrequent situation worldwide. In these systems, a new component is introduced, forest litter, which constitutes one of the main ways of incorporating carbon into the soil–plant system. The present work seeks to establish a methodological approach to study the dynamics of litter production and decomposition in an integrated way. The general objective was to characterize and compare the litter production dynamics in 14-year-old Eucalyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 75 publications
3
9
0
Order By: Relevance
“…According to the results from a previous study, there were not significant differences in the litter decomposition rate obtained from exponential decay models between the considered species and layers [5]. In this context, this study found that the nutrient dynamics differs enough to alter the average trend evidenced for biomass loss.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…According to the results from a previous study, there were not significant differences in the litter decomposition rate obtained from exponential decay models between the considered species and layers [5]. In this context, this study found that the nutrient dynamics differs enough to alter the average trend evidenced for biomass loss.…”
Section: Discussionsupporting
confidence: 56%
“…This situation allows to verify a more consistent trend, which is characterized by a greater enrichment of this metal in E. grandis. This context would explain the Zn immobilization processes identified in E. grandis and the oscillations between release and immobilization periods obtained in P. taeda, since there were no significant differences in the decomposition rate between species [5].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations